Relationship between the dimensions of the emotional competence profile and emotio-nal competence - Mendes, Carina Maria Pires (2024)
Recognize the relationships between Emotional Competence (EC) Profile and dimensions of the construct. Methods: A correlational study of the Emotional Competence Veiga Scale (ECVS) data, fom a 103 nursing students sample, the majority single (93.2%) and a small part married (2.9%), in an north-east of Portugal institution. The CE 5 dimensions of the construct, are operationalized along 112 items: each one operationalized through a Likert Scale with 7 cells, from 1 (never) to 7 (always), with the cutoff point at 4. The statistical analysis of data in SPSS allowing the EC global profile, to be drawn up using the five dimensions of the construct. and each dimension profile too. Results: The correlational analysis ® between the dimensions of EC and overall EC in the sample was determined the following: Firstly: Global EC shows a high and statistically significant correlation with Self-Awareness (SW) (r=0.755; p=0.000), emotion management (EM) (r=0.835; p=0.000), Self-Motivation (SM) (r=0.714; p=0.000), Empathy (E) (r=0.709; p=0.000) and Group Emotion Management (GEM) (r=0.725; p=0.000).